LOTUS: A low-cost time-lapse automated imaging system for spatio-temporal analysis of microbial colony or biofilm development - Ryunosuke Sakai; Yifan Zhao; Martin Robert (PLoS ONE, 2026)
The proliferation of low-cost single-board computers and 3D printers has considerably accelerated open science. In the life sciences, for both research and educational purposes, there is a growing trend to develop affordable imaging systems rather than purchasing specialized commercial instruments. However, existing solutions often lack diversity of imaging modes or adequate throughput. To fill this gap, we developed LOTUS, a low-cost (~$550 USD) automated imaging system built from 3-D printed components that integrates motorized sample positioning with interchangeable light-emitting diodes (LED) sources and optical filters for spatio-temporal analysis of microbial colony or biofilm development. LOTUS images up to nine samples at fixed time intervals (e.g., 20 min) in four modes: bright-field transillumination (biomass), bright-field epi-illumination (morphology), and dual-color epi-fluorescence (gene expression or other types of reporter analysis). Validation experiments demonstrated stable and reproducible timing and positioning accuracy over 3 days and homogeneity of LED illumination and captured images enabling semi-quantitative analysis. We demonstrated LOTUS capabilities by imaging E. coli biofilms expressing fluorescent reporter proteins (GFPmut2 and mCherry) over 5 days and tracking fluorescence intensity dynamics following sub-MIC ampicillin treatment. LOTUS represents a versatile and cost-effective semi-quantitative platform for parallel monitoring of colony or biofilm development and fluorescent reporter expression pattern. This open-source system makes automated time-lapse live imaging accessible for research and educational applications.